Indoor Off-Body Wireless Communication: Static Beamforming versus Space-Time Coding. (1st February 2012) - Van Torre, Patrick; Scarpello, Maria Lucia; Vallozzi, Luigi; Rogier, Hendrik; Moeneclaey, Marc; Vande Ginste, Dries; Verhaevert, Jo
Abstract : The performance of beamforming versus space-time coding using a body-worn textile antenna array is experimentally evaluated for an indoor environment, where a walking rescue worker transmits data in the 2.45 GHz ISM band, relying on a vertical textile four-antenna array integrated into his garment. The two transmission scenarios considered are static beamforming at low-elevation angles and space-time code based transmit diversity. Signals are received by a base station equipped with a horizontal array of four dipole antennas providing spatial receive diversity through maximum-ratio combining. Signal-to-noise ratios, bit error rate characteristics, and signal correlation properties are assessed for both off-body transmission scenarios. Without receiver diversity, the performance of space-time coding is generally better. In case of fourth-order receiver diversity, beamforming is superior in line-of-sight conditions. For non-line-of-sight propagation, the space-time codes perform better as soon as bit error rates are low enough for a reliable data link.